Introducing a student-led application of Google Expeditions: an exploratory study - Athanasiou, Androulla; Parmaxi, Antigoni; Demetriou, Alan A. (My University, 2021)
Technology integration in classroom settings has become a popular concept, especially due to the growth of the digital native population of learners and the novelty of technology tools. This exploratory study aimed at introducing a low-cost Virtual Reality kit, Google Expeditions, in a language classroom and explore its potential as a student-led tool for supporting language learning and teaching. The use of Google Expeditions was guided by teach-back, a pedagogical methodology which emphasises communication and comprehension through spoken interaction. Data were collected through interviews, focus groups, questionnaires, observations and video-taped sessions. Findings provide information on the patterns followed when pedagogically implementing Google Expeditions under teach-back. What is more, evidence is provided on how collaboration is encouraged and on the positive learning experiences of the students in the Google Expeditions sessions. Implications for researchers and instructional designers are also provided.
Keywords: Virtual reality; Google expeditions; Google cardboard; Teach-back